Desserts Enriched with a Nanoemulsion Loaded with Vitamin d3 and Omega-3 Fatty Acids for Older People - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The food industry is challenged to develop nutritious and palatable foods that satisfy older people’s needs. So, this work aimed to study the incorporation of nanoemulsions enriched with vitamin D3 and omega-3 fatty acids into two desserts (yogurt and fruit puree), characterizing their nutritional profile, viscosity, and color properties and evaluating their in vitro bioaccessibility and sensory response. The results showed that adding nanoemulsion modified the nutrition profile of desserts due to increasing lipids and calories. The desserts’ physical properties were also affected, with a decrease in viscosity and a lightening of color. Regarding digestion, the enriched desserts presented a low release of free fatty acids (14.8 and 11.4%, respectively). However, fruit puree showed the highest vitamin D3 and omega-3 fatty acid in vitro bioaccessibility (48.9 and 70.9%, respectively). In addition, older consumers found this dessert more acceptable than yogurt due to the adequate intensity of its sensory attributes (aroma, flavor, sweetness, and consistency). Therefore, the fruit puree can be enriched with nanoemulsions loaded with vitamin D3 and omega-3 fatty acids to improve the bioaccessibility of lipid bioactive compounds and sensory performance, offering a health-enhancing option for older consumers. © 2024 by the authors.